Fuzzy logic control based MPPT for standalone photovoltaic system with battery storage - Taib, Nur Syafiqah Mohd; Noor, Siti Zaliha Mohammad; Musa, Suleiman; Aziz, Pusparini Dewi Abd (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Considering its favorable characteristics, photovoltaic energy is widely recognized as highly beneficial to the environment. To achieve continuous maximum output power across the PV system, an efficient control strategy is developed after studying several maximum power point detection (MPPT) techniques. Consequently, this paper presents a useful control technique for maximizing power extraction from PV systems under varying conditions. The paper focuses on the design of a fuzzy logic control (FLC)-based maximum power point tracking (MPPT) system for a standalone photovoltaic (SAPV) system with battery storage. The FLC is employed to extract the maximum power from a PV module and integrate it with the battery to supply the load. The FLC offers advantages over conventional MPPT methods, such as accurate and rapid response to changes in environmental conditions, including solar irradiance and temperature. The PV system exhibits low total harmonic distortion (THD), making it ideal for household appliances, and can deliver 230 Vrms of single-phase output AC power. The system is designed and implemented in MATLAB/Simulink, incorporating a solar module, DC-to-DC converters, battery storage, and an inverter for supplying AC loads. Simulation results for selected test conditions are presented and discussed. The system performance is evaluated through steady state tests and dynamic tests in simulations.